An unusual communication between the mylohyoid and lingual nerves in man: Its significance in lingual nerve injury - Potu Bhagath; D′Silva Suhani; Thejodhar P; Jattanna Nishita (Wolters Kluwer Medknow Publications, 2010)
The mylohyoid nerve is the branch of the inferior alveolar nerve (IAN) which arises above the mandibular foramen. An abnormal communication between the mylohyoid nerve and lingual nerve (LN) was noted during the routine dissection of a male cadaver. Communicating branches between IAN and LN have been identified as a possible explanation for the inefficiency of mandibular anesthesia. The communication between mylohyoid and lingual nerve was found in this case after the LN passes in close relation to third molar tooth, which makes it more susceptible to injury during third molar extractions.